Сучасний стан торгівлі цінними паперами на світовому фондовому ринку - Белінська, Яніна Василівна; Бобровник, Вікторія Миколаївна; Белінська, Яніна (Причорноморський науково-дослідний інститут економіки та інновацій, 2021)
У статті висвітлено роль світового фондового ринку у розвитку як окремої держави, так і світової економіки у цілому. Охарактеризовано місце фондового ринку як одного з найважливіших складників світового фінансового ринку. Визначено, як та за яких умов працює фондовий ринок, його основні особливості та функції. Окреслено основні тенденції розвитку світового фондового ринку в умовах глобалізації світового господарства. Визначено перспективи розвитку основних фондових бірж світу. Здійснено комплексний аналіз динаміки світового фондового ринку за останні п’ять років. Висвітлено структуру інвестиційних потоків світового фондового ринку. Охарактеризовано та проаналізовано середньодобовий оборот обсягу торгівлі цінними паперами на світовому фондовому ринку. Проаналізовано зміну обсягів капіталізації найбільших світових фондових бірж за останні п’ять років. Визначено сучасний фондовий ринок як ринок, що є доволі динамічним та знаходиться в постійному русі.

The article examines the role of the global stock market in the development of both the individual state and the world economy as a whole. Since today the stock market is one of the most important buffers for the formation and use of investment resources by all economic entities, the main prerequisite for its sustainable development and efficient operation is a favorable economic situation in the country, widespread network of stock exchanges, high confidence and the population to stock market instruments. The place of the stock market as one of the most important components of the world financial market is described. The global stock market can be represented as a mechanism that allows the exchange of financial assets between countries and that shapes their prices. The development of information transfer technologies, new means of payment and assets make significant adjustments to the mechanism of functioning of modern financial markets. In recent years, the global financial market has undergone significant structural changes that have radically changed the conditions and features of their operation, so a comprehensive analysis of the dynamics of the global stock market over the past five years. The globalization of the world economy has led to significant changes in the stock market, such as a significant increase in the size of the international investment market and an increase in the share of portfolio and speculative investors. Acceleration of globalization processes, which are becoming a characteristic feature of modernity, requires a study of the peculiarities of the entry of national markets into the international investment space, so highlighted the structure of investment flows in the global stock market. Uncertainty of the environment, which is a fundamental characteristic of the modern socio-economic system, creates financial shocks and directly proportionally affects the state of securities trading in the global stock market, so the assessment of the leading countries in the world stock market. stock market capitalization. The change in the capitalization of the world's largest stock exchanges over the past five years has been analyzed.
Keywords: світовий фондовий ринок; капіталізація; цінні папери; фондова біржа; інвестиційні потоки; world stock market; capitalization; securities; stock exchange; investment flows